Colorectal Adenocarcinoma Metastasis to the Tongue - Kurren S. Gill; Mark A. Frattali (Case Reports in Otolaryngology)
This case presentation examines a rare clinical entity: colorectal adenocarcinoma (CRC) metastasis to the tongue. CRC is among the least common tumors to metastasize to the oral cavity. Objectives for this case report are to (1) maintain a high index of suspicion for oral cavity tumors representing metastatic disease, (2) consider appropriate surgical and adjunctive interventions, and (3) recognize the significance of identifying the primary tumor via immunohistochemical staining. We present a case of a 57-year-old male with a history of stage IV rectal adenocarcinoma metastatic to the lung who presented to our clinic with a painful mass of the right lateral tongue that he noticed one month before. MRI of the neck revealed a mass involving the anterior two-thirds of the right tongue with irregular margins and an ipsilateral enlarged right jugulodigastric lymph node. The patient underwent right partial glossectomy with primary reconstruction and right modified radical neck dissection. Pathology confirmed poorly differentiated adenocarcinoma consistent with a colorectal primary with lymphovascular and perineural invasion. The tumor was staged as T2N1, and the patient was referred for chemoradiation. In this report, we discuss the presentation, diagnosis, and treatment of this uncommon disease, with a thorough review of the world literature.